Identification of resistance to Sugarcane mosaic virus, Sugarcane streak mosaic virus, and Sugarcane bacilliform virus in new elite sugarcane accessions in India - Vamsi Krishna, G.; Manoj Kumar, V.; Kishore Varma, P.; Bhavani, B.; Vijaya Kumar, G. (Frontiers in Microbiology, 2023)
Sugarcane mosaic and leaf fleck diseases are significant viral diseases affecting sugarcane crop in India. The use of resistant sugarcane varieties is considered the most economical and effective approach to manage viral diseases, especially in vegetatively propagated crops like sugarcane. Sugarcane mosaic virus (SCMV) and Sugarcane streak mosaic virus (SCSMV) are the primary pathogens responsible for mosaic disease in sugarcane-growing regions of India. Sugarcane bacilliform virus (SCBV), causing leaf fleck disease, is also often found in mixed infections with mosaic symptoms. The study aimed to identify new sources of resistance by screening sugarcane germplasm for resistance to SCMV, SCSMV, and SCBV. The screening was carried out under high inoculum using infector row method in both plant and ratoon crops. Out of 129 genotypes tested, only 8 were found to be free of mosaic viruses, indicating a rare occurrence of resistant sources. The study revealed that mosaic disease is widespread, with nearly 95% of tested varieties/genotypes being infected with mosaic viruses. SCMV, SCSMV, and SCBV were detected in 121 out of 129 genotypes using RT-PCR and PCR assays. Based on their response to the viruses, the tested genotypes were categorized into different resistance grades: highly resistant (grade 1), resistant (grade 2), moderately resistant (grade 3), susceptible (grade 4), and highly susceptible (grade 5). The results of the study provide valuable information about elite resistance resources that can be used for the prevention and control of mosaic disease. These resistant genotypes could also serve as potential donors for mosaic and leaf fleck disease resistance in breeding program.